Sigma factors, asymmetry, and the determination of cell fate in Bacillus subtilis. - Lewis, P J (1994)
Soon after the initiation of sporulation, Bacillus subtilis divides asymmetrically to produce sister cells that have very different developmental fates. Recently, it has been proposed that the differential gene expression which begins soon after this division is due to cell-specific activation of the transcription factors sigma F and sigma E in the prespore and the mother cell, respectively. We describe the use of a method for the localization of gene expression in individual sporulating cells that lends strong support to the cell-specific localization of sigma F and sigma E activities. The dependence of sigma E activity on integrity of the gene encoding sigma F has led to the suggestion that activation of sigma F in the prespore leads to a directional signal that triggers activation of sigma E only in the mother cell. Here we show that sigma E actually specifies the fate of the mother cell; in the absence of sigma E, two prespore-like cells are made. The appearance of sigma F activity at both poles of a sigma E-deficient mutant supports the idea that sigma F normally remains latent in the mother cell and that its activation depends on some morphological or physiological feature of the prespore. We present a model for the generation of asymmetry and the establishment of cell fate in B. subtilis.